2010
DOI: 10.1186/1472-6963-10-322
|View full text |Cite
|
Sign up to set email alerts
|

Improving district level health planning and priority setting in Tanzania through implementing accountability for reasonableness framework: Perceptions of stakeholders

Abstract: BackgroundIn 2006, researchers and decision-makers launched a five-year project - Response to Accountable Priority Setting for Trust in Health Systems (REACT) - to improve planning and priority-setting through implementing the Accountability for Reasonableness framework in Mbarali District, Tanzania. The objective of this paper is to explore the acceptability of Accountability for Reasonableness from the perspectives of the Council Health Management Team, local government officials, health workforce and member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Contextual factors such as described in the present study are more likely to be somewhat found at the local level in several low-and middle income countries, as reported in existing literature from Benin [23, 51], Burundi [48], Uganda [58], Tanzania [60] and India [26, 44]. This highlights that the conceptual model as adapted can be used in other setting in order to generate information about local contexts.…”
Section: Discussionsupporting
confidence: 61%
“…Contextual factors such as described in the present study are more likely to be somewhat found at the local level in several low-and middle income countries, as reported in existing literature from Benin [23, 51], Burundi [48], Uganda [58], Tanzania [60] and India [26, 44]. This highlights that the conceptual model as adapted can be used in other setting in order to generate information about local contexts.…”
Section: Discussionsupporting
confidence: 61%
“…In many ways, this process met the criteria of the accountability for reasonableness (25)(26)(27) process. In many ways, this process met the criteria of the accountability for reasonableness (25)(26)(27) process.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of pharmacy support workers and community health workers involved in medicine supply and distribution, as a result of task sharing and task shifting to mitigate shortages of pharmacists and improve access to essential medicines, reinforces the importance of the supervisory role [8]. In Tanzania, district pharmacists were involved in planning, budgeting, management and support of health services in the district [9]. However, in most countries, there is little specific information about district pharmacists’ responsibilities and how they function within the management team.…”
Section: Introductionmentioning
confidence: 99%